Economic Organization and Imperfect Managerial Knowledge: A Study of the Role of Managerial Meta-Knowledge in the Management of Distributed Knowledge - Henrik Jensen (Copenhagen Business School (CBS), 2016)
When companies depend on knowledge distributed among employees, managers play a key role in establishing cooperation and coordination systems. This dissertation investigates the implications of managers' knowledge about the knowledge and skills of employees for economic organization. The research question guiding this effort is: What managerial challenges arise from having distributed knowledge within a firm and how does the manager's knowledge of this knowledge matter for economic organization? The dissertation consists of three research papers, each exploring a dimension of the research question. The first paper investigates antecedents of coordination break-down and how teams differ in their ability to coordinate specialized knowledge and skills. The second paper provides a theoretical framework for theorizing about the role of managers' knowledge about employees' knowledge for economic organization and introduces the term managerial meta-knowledge. The third paper investigates the effect of managerial meta-knowledge on the successfulness of inter-organizational relations. Empirically, the dissertation is based on a dataset on public procurement projects, comprised of archival data, a survey of buyers and a survey of suppliers. Together, the three papers argue that managers' knowledge about employees' knowledge is an important factor when managing the challenges of distributed knowledge. Such managerial knowledge allows managers to assess the capabilities available, make sure they fit contractual obligations, and rearrange tasks and employees when adapting to changes.
hdl:10398/9375
Keywords: 650